Penicillin tolerance in Streptococcus faecium ATCC 9790. - Said, I (1987)
Tolerant strains of Streptococcus faecium had higher levels of muramidase 2 and lower levels of trypsinactivable muramidase 1 than did susceptible strains. Susceptible strains lysed faster than did tolerant strains in buffer and at some antibiotic concentrations. The addition of Triton X-100 produced equal lysis rates for susceptible and tolerant cultures.